Detection, survival and infectious potential of Mycobacterium tuberculosis in the environment: a review of the evidence and epidemiological implications. Issue 6 (27th June 2019) - Martinez, Leonardo; Verma, Renu; Croda, Julio; Horsburgh, C. Robert; Walter, Katharine S.; Degner, Nicholas; Middelkoop, Keren; Koch, Anastasia; Hermans, Sabine; Warner, Digby F.; Wood, Robin; Cobelens, Frank; et al.
Much remains unknown about Mycobacterium tuberculosis transmission. Seminal experimental studies from the 1950s demonstrated that airborne expulsion of droplet nuclei from an infectious tuberculosis (TB) patient is the primary route of transmission. However, these findings did not rule out other routes of M. tuberculos is transmission. We reviewed historical scientific evidence from the late 19th/early 20th century and contemporary studies investigating the presence, persistence and infectiousness of environmental M. tuberculosis . We found both experimental and epidemiological evidence supporting the presence and viability of M. tuberculosis in multiple natural and built environments for months to years, presumably following contamination by a human source. Furthermore, several studies confirm M. tuberculosis viability and virulence in the environment using guinea pig and mouse models. Most of this evidence was historical; however, several recent studies have reported consistent findings of M. tuberculosis detection and viability in the environment using modern methods. Whether M. tuberculosis in environments represents an infectious threat to humans requires further investigation; this may represent an untapped source of data with which to further understand M. tuberculosis transmission. We discuss potential opportunities for harnessing these data to generate new insights into TB transmission in congregate settings. Although airborne transmission is accepted as the primary mechanistic route of Mycobacterium tuberculosis, there is a high-quality scientific evidence base supporting the presence, persistence and infectiousness of M. tuberculosis in the environment http://bit.ly/2VwoSnK